2018
DOI: 10.14712/23366052.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and somatotype differences between C1 paddlers who were and were not selected for the Czech national team

Abstract: The objective of this study was to determine the anthropometric and somatotype differences between elite single-canoeists (C1) included in the white-water slalom Czech national team (NT) (n = 5) and others (n = 12) who did not qualify for the national team (DNQ) leading up to the Olympic Games in Rio de Janiero, 2016. All paddlers were measured using a battery of 40 anthropometric parameters in one day, 4 weeks before competing in the Czech national selection races. The NT racers had a significantly (p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(28 reference statements)
1
4
1
Order By: Relevance
“…Male and female slalom athletes are considered predominantly mesomorphic (Ridge et al). A recent study, however, reported that international male canoeists body weight (76.2 ± 4.4), somatotype (1.4 -5.6 -2.3) and girth of flexed arm (35.6 ± 1.5) (Busta et al, 2018) were different to that of earlier research (Ridge et al).…”
Section: Introductioncontrasting
confidence: 69%
“…Male and female slalom athletes are considered predominantly mesomorphic (Ridge et al). A recent study, however, reported that international male canoeists body weight (76.2 ± 4.4), somatotype (1.4 -5.6 -2.3) and girth of flexed arm (35.6 ± 1.5) (Busta et al, 2018) were different to that of earlier research (Ridge et al).…”
Section: Introductioncontrasting
confidence: 69%
“…Therefore, this is indicative that their physique is better adapted to canoe slalom because they can maximize upper-body muscle hypertrophy while at the same time they can maintain low hypertrophy of the lower body. In supporting this Busta et al (2018) reported body weight should not exceed 80 kg for all international level canoe slalom paddlers. Body weight over 80 kg for international level paddlers is very rare, from the current sample population (n=48) only 5 competitors exceeded 80 kg, with a maximum weight was 85.3 kg.…”
Section: Discussionmentioning
confidence: 77%
“…Canoe slalom competition preserves the unpredictability (Nibali et al, 2011) and therefore it is difficult to find strong performance predictors. Previous research showed significant and medium high correlations between strength tests (e.g., 1-RM bench-press, 30 seconds peak power in arm-crank Wingate test) (Busta et al, 2018) and significant differences between the athletes who were and were not selected to the national team in strength-related anthropometric parameters such as, flexed arm girth, forearm girth, and chest girth (Busta et al, 2018). Significant strong correlations have been observed between upper arm girth and short distance performance in canoe sprint (Akca & Muniorglu, 2008) and between upper and forearm girth in canoe/kayak ergometer performance test (Hamano et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…This agility is based, among other things, on a high level of fitness, in particular a high level of relative strength, which is in relation to body weight ( Busta and Suchý, 2016 ). In male athletes, physiological differences between performance levels are described—successful male athletes achieve significantly higher levels of relative strength (strength/body weight ratio) and special endurance represented by specific on-water tests ( Busta et al, 2018a ; Vajda and Piatrikova, 2022 ) but not in aerobic power tested by treadmill running ( Bielik et al, 2021 ). Therefore, it is not surprising that significant factors in canoe slalom are body size (body measurements and proportions) and body composition ( Messias et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The elite male athletes are, on average, tall; their body weight is approximately 75 kg and only rarely exceeds 80 kg ( Coufalová et al, 2021 ). They have very well-developed musculature in the trunk and upper limbs, a low body fat percentage, and low muscle volume in the lower limbs ( Busta et al, 2018a ; Coufalová et al, 2021 ; Busta et al, 2022 ). We conclude that anthropometric parameters are very well-studied in men: we know the differences between C1 and K1 paddlers ( Coufalová et al, 2021 ) and also between the highest international performance-level paddlers (including only Olympic and World Championship medalists) and international performance-level paddlers (including remaining World Cup racers) ( Busta et al, 2022 ), national team competitors and other competitors ( Busta et al, 2018b ), or junior and senior paddlers ( Busta and Suchý, 2016 ).…”
Section: Introductionmentioning
confidence: 99%